Pollination of Ophrys (Orchidaceae) and pseudo-copulation of Hymenoptera males (Bollettino di zoologia agraria e bachicoltura, 2024)
The close specific relationships between flowers and insects have been dealt with in extensive and fascinating research works ever since the discovery of the fundamental role played by plant odours perceived by insects. This new chapter opens up prospects for the understanding of these special relationships and a tentative determination of their ontologica! meaning.The relationships between Ophrys flowers and various Hymenoptera such as Apoidea, Vespoidea and Sphecoidea are characterized by an additional extremely curious phenomenon: the pseudo-copulation, some parts of the flower being perceived by the male insect as an appealing female in desire of copulation.The attitude taken then by the male ensures one of the essential sequences to transfer pollinia from a first flower to another.Flower organization and biology of Ophrys, as well as sexual behaviour of Hymenoptera are described as an introduction to the description of recent works on flower attractive factors and on their results. The odours identified to date, released either by plants or by pollinating insects, are described along with the many worldwide experiments on this topic.
Keywords: pollination; Ophrys; pseudo-copulation; Hymenoptera